EFEKTIVITAS LEMBAR KERJA BERBASIS KECERDASAN VISUAL SPASIAL DAN LOGIS TERHADAP PEMAHAMAN KONSEP MATEMATIS - Pratama, Elvandri Yogi (LPPM STKIP PGRI Bandar Lampung, 2019)
This study aims to develop effective worksheets based on visual-spatial and logical mathematical intelligence that are effective in understanding students' concepts. Student worksheets are developed based on material criteria and the intelligence background of students. Student worksheets are designed using language or instructions that are easy for students to understand. Students are directed to find concepts independently, and the origin of a concept is obtained by utilizing the intelligence they have. Research on this development is only limited to the test phase. The subjects in this study are seventh-grade students in the first semester of SMP Negeri 2 Merbau Mataram in the academic year 2018/2019. The instrument used in this study is a conceptual understanding test instrument that is used to see the effectiveness of the worksheets of students developed. An assessment of the understanding of students' concepts is carried out based on the scoring guidelines that have been made. The results of the research and discussion show that the worksheets of students developed are very practical in terms of understanding the concepts of students.